2018
DOI: 10.1093/jas/skx064
|View full text |Cite
|
Sign up to set email alerts
|

Preslaughter handling practices and their effects on animal welfare and pork quality1

Abstract: At all times, prior to slaughter, pigs may experience stress from a range of handling practices, such as fasting, loading and transport, mixing, and interaction with humans. These factors can affect the welfare of pigs and carcass and meat quality, both individually and collectively. Preslaughter stress is both an animal welfare and a meat quality issue. Behavioral and physiological studies have revealed that poor handling practices at the farm, during transport and at the slaughter plant, have an adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 80 publications
1
59
0
3
Order By: Relevance
“…The color of pork is influenced by multiple factors, such as feed, pre-slaughter handling, genetics, age, anatomical function of the muscle, amount of oxidative and glycolytic metabolism, mixed fibers, and sex Arkfeld et al 2017;Faucitano, 2018). A study of the color of muscles showed that the SM muscle of castrated males and females produced under the same conditions did not show differences in L*, a*, and b*, indicating no effect of sex (Overholt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The color of pork is influenced by multiple factors, such as feed, pre-slaughter handling, genetics, age, anatomical function of the muscle, amount of oxidative and glycolytic metabolism, mixed fibers, and sex Arkfeld et al 2017;Faucitano, 2018). A study of the color of muscles showed that the SM muscle of castrated males and females produced under the same conditions did not show differences in L*, a*, and b*, indicating no effect of sex (Overholt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was observed that some loads (26 shipments, corresponding to 59% of loads) were slaughtered within few hours after unloading, of which one was slaughtered immediately after unloading (minimum lairage duration of 3 min), whereas others (18 shipments, corresponding to 41% of loads) were kept in lairage overnight (lairage duration above 10 h). Although there is a certain degree of contradiction among studies about the definition of optimal lairage duration in relation to its effects on meat quality [29], a lairage of 2-3 h is generally recommended [4]. It has been observed that, in the case of heavy pigs, overnight lairage may increase the risk of pre-slaughter animal losses [15], although this effect seems to be largely dependent on the characteristics of the slaughterhouse such as stocking density, presence of large open windows, and use of sprinklers as cooling devices [28].…”
Section: General Characteristics Of the Shipmentsmentioning
confidence: 99%
“…This result may indicate a higher degree of muscle damage in the HS cluster pigs, which may be associated to the factors characterizing the HS cluster. All these characteristics result in acute stress and fatigue [1,4,40]. For example, long journeys, group mixing and accidents during handling may cause both direct (traumatic) and indirect (fatigue-induced) muscle damage (therefore leading to an increase in serum leaking enzymes), together with an increase in the stress response.…”
Section: Hs 1 Lsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same method, Tomovic et al (2014) introduced for the Landrace and Large White breeds and WHC is influenced by the muscular type. WHC is an important attribute in the industry as it is important for the yield of processed and stained products of fresh meat The color of pork is influence by multiple factors such as feed, pre-slaughter handling, genetics, age, anatomical function of the muscle, amount of oxidative, glycolytic, mixed fibers, and sex Arkfeld et al 2017;Faucitano, 2018). A study of the color of some muscles showed that the SM muscle of castrated males and females produced under the same conditions did not show differences in L*, a*, and b*, indicating no effect of sex (Overholt et al, 2016).…”
Section: Resultsmentioning
confidence: 99%